2001
DOI: 10.1111/j.1442-2050.2001.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the rat esophagus in the presence of a proton pump inhibitor: a pilot study

Abstract: This study examines the effects of a proton pump inhibitor on a rat model of duodenogastric reflux. Duodenoesophageal reflux was induced in 60 rats by performing a duodenesophagostomy. The study group received daily intraperitoneal injections of a proton pump inhibitor for 6 months and the control group received an equivalent injection of saline. Rats were examined at death for macroscopic tumor, dysplasia, adenocystic changes, papillomatosis, and adenocarcinoma. Five out of 19 rats in the study group and thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Minimally invasive surgery, with better immediate results as in this study, even good late results in normal children, and better results in NI children, in comparison with open surgery, has been confirmed to be a good therapeutic option. Indeed, side effects of some medical treatments after long utilization are potentially very high [5,19]. This type of managment, certainly in children, has to be honestly compared to that of laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive surgery, with better immediate results as in this study, even good late results in normal children, and better results in NI children, in comparison with open surgery, has been confirmed to be a good therapeutic option. Indeed, side effects of some medical treatments after long utilization are potentially very high [5,19]. This type of managment, certainly in children, has to be honestly compared to that of laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…20,44 The long-term effects of proton pump inhibitor therapy on the cancer risk from Barrett's metaplasia are not yet known, and studies on animal models of reflux have yet to show any reduction in cancer risk following proton pump inhibitor treatment. 36,45 The effect of proton pump inhibitor therapy on surrogate clinical markers of cancer risk has been assessed, including major regression in the total surface area of metaplastic epithelium 18 and prevention of progression to dysplasia. In a small randomized controlled trial, treatment with omeprazole produced a statistically significant regression in Barrett's surface area (average of 9% of the mucosal area), compared with histamine-2 receptor antagonist treatment.…”
Section: Acid Bile and The Drive For Metaplastic Changementioning
confidence: 99%
“…Several animal models examined the effect of PPI therapy on DGER. Moore et al (2001) found that the addition of omeprazole did not increase the number of esophageal adenocarcinomas in animals that underwent different forms of surgical reflux to maximize DGER (Netzer et al, 2001). In contrary Nasr et al, 2006) demonstrated that the use of acid suppression therapy in the presence of duodenal refluxate caused increased rates of inflammatory changes, intestinal metaplasia and molecular proliferative activity.…”
Section: Role Of Medication In the Control Of Dgermentioning
confidence: 96%
“…Although none of the rats developed oesophageal cancer, oesophageal mucosal hyperplasia was more pronounced when compared to surgery alone group. Moore et al (2001) performed duodenoesophagostomy on rats to induce duodenal reflux. They treated the study group with a daily intra-peritoneal dose of omeprazole and the control group with normal saline for 6 months.…”
Section: Science Publicationsmentioning
confidence: 99%
See 1 more Smart Citation